A Photocleavable Contrast Agent for Light-Responsive MRI - Friederike Reeßing; Sèvrin E. M. Huijsse; Rudi A. J. O. Dierckx; Ben L. Feringa; Ronald J.H. Borra; Wiktor Szymański (MDPI AG, 2020)
Thanks to its innocuousness and high spatiotemporal resolution, light is used in several established and emerging applications in biomedicine. Among them is the modulation of magnetic resonance imaging (MRI) contrast agents' relaxivity with the aim to increase the sensitivity, selectivity and amount of functional information obtained from this outstanding whole-body medical imaging technique. This approach requires the development of molecular contrast agents that show high relaxivity and strongly pronounced photo-responsiveness. To this end, we report here the design and synthesis of a light-activated MRI contrast agent, together with its evaluation using UV-vis spectroscopy, Fast Field Cycling (FFC) relaxometry and relaxometric measurements on clinical MRI scanners. The high relaxivity of the reported agent changes substantially upon irradiation with light, showing a 17% decrease in relaxivity at 0.23T upon irradiation with λ = 400 nm (violet) light for 60 min. On clinical MRI scanners (1.5T and 3.0T), irradiation leads to a decrease in relaxivity of 9% and 19% after 3 and 60 min, respectively. The molecular design presents an important blueprint for the development of light-activatable MRI contrast agents.